Peptide-Bound Methionine Sulfoxide (MetO) Levels and MsrB2 Abundance Are Differentially Regulated during the Desiccation Phase in Contrasted Acer Seeds - Natalia Wojciechowska; Shirin Alipour; Ewelina Stolarska; Karolina Bilska; Pascal Rey; Ewa Marzena Kalemba (Antioxidants, 2020)
Norway maple and sycamore produce desiccation-tolerant (orthodox) and desiccation-sensitive (recalcitrant) seeds, respectively. Drying affects reduction and oxidation (redox) status in seeds. Oxidation of methionine to methionine sulfoxide (MetO) and reduction via methionine sulfoxide reductases (Msrs) have never been investigated in relation to seed desiccation tolerance. MetO levels and the abundance of Msrs were investigated in relation to levels of reactive oxygen species (ROS) such as hydrogen peroxide, superoxide anion radical and hydroxyl radical (•OH), and the levels of ascorbate and glutathione redox couples in gradually dried seeds. Peptide-bound MetO levels were positively correlated with ROS concentrations in the orthodox seeds. In particular, •OH affected MetO levels as well as the abundance of MsrB2 solely in the embryonic axes of Norway maple seeds. In this species, MsrB2 was present in oxidized and reduced forms, and the latter was favored by reduced glutathione and ascorbic acid. In contrast, sycamore seeds accumulated higher ROS levels. Additionally, MsrB2 was oxidized in sycamore throughout dehydration. In this context, the three elements •OH level, MetO content and MsrB2 abundance, linked together uniquely to Norway maple seeds, might be considered important players of the redox network associated with desiccation tolerance.